Scale and the origins of structural change - Francisco J. Buera; Joseph P. Kaboski (Federal Reserve Bank of Chicago, 2008)
Structural change involves a broad set of trends: (i) sectoral reallocations, (ii) rich movements of productive activities between home and market, and (iii) an increase in the scale of productive units. After extending these facts, we develop a model to explain them within a unified framework. The crucial distinction between manufacturing, services, and home production is the scale of the productive unit. Scale technologies give rise to industrialization and the marketization of previously home produced activities. The rise of mass consumption leads to an expansion of manufacturing, but a reversal of the marketization process for service industries. Finally, the later growth in the scale of services leads to a decline in industry and a rise in services.
Keywords: 330; Strukturwandel; Betriebsgröße; Auslandsverlagerung; Theorie; Welt; USA